2023
DOI: 10.1002/ldr.4188
|View full text |Cite
|
Sign up to set email alerts
|

From expansion to shrinkage: Exploring the evolution and transition of karst rocky desertification in karst mountainous areas of Southwest China

Abstract: Systematic elucidation of the evolution trend of karst rocky desertification (KRD) is of great significance for correctly understanding its occurrence and development process, and implementing effective comprehensive control measures. Based on the existing studies, the authors explore the formation and evolutionary mechanisms and trends of KRD in the karst mountains of Southwest China based on literature induction and field investigations. The factors driving the occurrence and formation of KRD are the single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…In addition, vegetation restoration can control soil erosion. Vegetation cover can effectively reduce the scouring of soil by water flow, stabilize soil particles and stop slope failure and landslides, thus reducing the risk of soil erosion (Li et al, 2022c; Wang et al, 2004). Therefore, it has been shown that the hydrological effect of vegetation restoration on soil water in karst areas is mainly in the form of its ability to increase soil water conservation capacity, which will also change soil properties and vegetation characteristics.…”
Section: Hydrological Effects Of Vegetation Restoration In Karst Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, vegetation restoration can control soil erosion. Vegetation cover can effectively reduce the scouring of soil by water flow, stabilize soil particles and stop slope failure and landslides, thus reducing the risk of soil erosion (Li et al, 2022c; Wang et al, 2004). Therefore, it has been shown that the hydrological effect of vegetation restoration on soil water in karst areas is mainly in the form of its ability to increase soil water conservation capacity, which will also change soil properties and vegetation characteristics.…”
Section: Hydrological Effects Of Vegetation Restoration In Karst Areasmentioning
confidence: 99%
“…This part analyzes the effects of vegetation restoration on individual elements of the hydrological cycle and the overall hydrological cycle in the karst region. Specifically, current studies on the hydrological effects of karst vegetation restoration have focused on the response of soil moisture, evapotranspiration, runoff (surface-subsurface runoff), water use efficiency, flow production and catchment processes to them (Deng et al, 2020;Li et al, 2022c;Liu et al, 2022;Luo et al, 2023;Peng et al, 2022;Wang et al, 2004Wang et al, , 2023Xiao et al, 2023;Yan et al, 2023;Zhou et al, 2022). Studies have explored the role of vegetation restoration in regulating river flow in karst areas, put forward the significance of karst vegetation restoration on water conservation and storage, and revealed the differences in hydrological effects of vegetation restoration in karst areas (Cheng et al, 2013;Hoek van Dijke et al, 2022;Hou and Gao, 2019;Sterling et al,2013).…”
Section: Hydrological Effects Of Vegetation Restoration In Karst Areasmentioning
confidence: 99%
“…Anthropogenic activities beyond the ecological threshold are the primary cause of eco‐degradation (Cao et al, 2021; Li et al 2022b), for example, the expansion of KD (Figure 1a). The reduction of human disturbances contributes to land function transformation and vegetation restoration (Wang et al, 2019a; Zhao et al, 2021), such as the shrinkage of KD (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…The essence is the expansion of forests to replace farmland, manifested by rapid greening. Finally, KD begins to shrink (Li, 2021; Li et al 2022b). In degraded ecoregion, farmers prefer to choose non‐farm work because of the low farming income (Liu, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable management and ecological protection of cultivated land have always been hot topics of concern for the government and academia. The ecological environment in the KMA of Southwest China is fragile, recovering gradually from economic backwardness, land degradation (KRD), and ecological damage(Li et al, 2022), always with ecological and economic sustainability as the development goal. In the future evolution of SCL, relevant departments should implement land use and ecological protection policies according to local conditions to promote the evolution of SCL in an ecologically sustainable direction (Figure13).…”
mentioning
confidence: 99%